2014
DOI: 10.1590/s0036-46652014000400009
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Antibiotics in Urinary Tract Infections in a Secondary Care Setting From 2005-2006 and 2010-2011, in São Paulo, Brazil: Data From 11,943 Urine Cultures

Abstract: Introduction: Urinary tract infection (UTI) has a high incidence and recurrence, therefore, treatment is empirical in the majority of cases. Objectives: The aim of this study was to analyze the urine cultures performed at a secondary hospital, during two periods, 2005-2006 and 2010-2011, and to estimate the microbial resistance. Patients and methods: We analyzed 11,943 aerobic urine cultures according to basic demographic data and susceptibility to antibiotics in accordance with the Clinical and Laboratory Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
6
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
5
6
0
1
Order By: Relevance
“…5b) results indicated that the MIC value corresponded to the µ-drug cocktail from outlet 5. The µ-drug cocktail exhibited normalized growth of~5%, corresponding to a ciprofloxacin concentration of~50 µg/L, which is in agreement with the documented range for similar known multidrug AMR strains of E. coli 74,76 . Solutions containing higher concentrations of tetracycline showed roughly the same amount of growth, whereas those containing lower concentrations of ciprofloxacin show increased amounts of growth, ≤~50%.…”
Section: Single-antibiotic Mic Testingsupporting
confidence: 84%
See 1 more Smart Citation
“…5b) results indicated that the MIC value corresponded to the µ-drug cocktail from outlet 5. The µ-drug cocktail exhibited normalized growth of~5%, corresponding to a ciprofloxacin concentration of~50 µg/L, which is in agreement with the documented range for similar known multidrug AMR strains of E. coli 74,76 . Solutions containing higher concentrations of tetracycline showed roughly the same amount of growth, whereas those containing lower concentrations of ciprofloxacin show increased amounts of growth, ≤~50%.…”
Section: Single-antibiotic Mic Testingsupporting
confidence: 84%
“…Amikacin is a particularly effective antibiotic in combination treatments used to combat infections such as serious UTIs, tuberculosis and bacterial meningitis, and AST evaluation of amikacin is frequently performed in clinical and drug development settings 16,[76][77][78][79] . The results from the amkacin-buffer-buffer gradient (Fig.…”
Section: Single-antibiotic Mic Testingmentioning
confidence: 99%
“…This may be related to the fact that females between 15 and 64 years are the group most commonly affected by urinary tract infection, a major cause of empiric oral antibiotic use and thus of AMR. [26] Not only antibiotic consumption was greater, but the policy was also found to be more effective in those municipalities with a higher percentage of females, possibly reducing the OTC use of antibiotic for this infection.…”
Section: Discussionmentioning
confidence: 99%
“…[21] There are, however, few studies on variations in antibiotic use within SSP and their SED, with these studies usually focusing on single or few municipalities. [2226] There are also little data about the levels and the evolution of AMR within SSP. Kiffer et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation